Regulation of the plasma amino acid profile by leucine via the system L amino acid transporter. Issue 12 (2nd December 2015) - Zhen, Hongmin; Nakamura, Koichi; Kitaura, Yasuyuki; Kadota, Yoshihiro; Ishikawa, Takuya; Kondo, Yusuke; Xu, Minjun; Shimomura, Yoshiharu
Abstract: Plasma concentrations of amino acids reflect the intracellular amino acid pool in mammals. However, the regulatory mechanism requires clarification. In this study, we examined the effect of leucine administration on plasma amino acid profiles in mice with and without the treatment of 2-aminobicyclo-(2, 2, 1)-heptane-2-carboxylic acid (BCH) or rapamycin as an inhibitor of system L or mammalian target of rapamycin complex 1, respectively. The elevation of plasma leucine concentration after leucine administration was associated with a significant decrease in the plasma concentrations of isoleucine, valine, methionine, phenylalanine, and tyrosine; BCH treatment almost completely blocked the leucine-induced decrease in plasma amino acid concentrations. Rapamycin treatment had much less effects on the actions of leucine than BCH treatment. These results suggest that leucine regulates the plasma concentrations of branched-chain amino acids, methionine, phenylalanine, and tyrosine, and that system L amino acid transporters are involved in the leucine action. Abstract: : The elevation of leucine concentration in cells promotes the influx of BCAAs, methionine, phenylalanine, and tyrosine into cells through the LAT.